The Anatomy of Asian Palm Civet (Paradoxurus hermaphroditus) Brain in Timor Island - Filphin Adolfin Amalo; Yulfia Nellymalik Selan; Antin Yeftanti Nugrahening Widi; Andry Ndula Rimu (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
Asian palm civet (Paradoxurus hermaphroditus) is native to some Asian regions, include Indonesia. Despite its wide spreading in those areas, study in regards to its anatomy is very few. This study is aimed to unveil the anatomy of Asian plam civet brain in Timor island. This study was performed in three Asian palm civets. The palm civets were anesthesized and humanely euthanazied using perfusion technique, and macroscopically observed for their brains anatomy.  Results showed Asian palm civet consisted of three main parts which were cerebrum, cerebellum, and brain stem. Compared to brain of dog, sulci and gyri of the Asian palm civet is simpler, with paraflocculus lobes were merely located in dorsal and ventral parts of the brain. However, the vermis was more similar to dogs, and more developed compare to Reusettussp (Javanese codot). This suggests that the anatomical difference is a result of the different behavior, which are nocturnal animal and live on trees.